ARTIFICIAL INTELLIGENCE (AI)-INTEGRATED CIVIC EDUCATION FOR ENHANCING CIVIC LITERACY AND CRITICAL THINKING AMONG STUDENTS AT SMAN 1 SLEMAN - Salsabila, Ghina; Marzuki, Marzuki; Marsiswandi, Marsiswandi (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2026)
This study aims to analyze the transformation of Pancasila and Civic Education (PPKn) learning through the integration of Artificial Intelligence (AI) in enhancing students' civic literacy and critical thinking at SMAN 1 Sleman. The Society 5.0 era requires students to not only be technologically proficient but also possess an ethical filter and strong civic character. This research employs a descriptive qualitative approach, with data collection techniques including observation, in-depth interviews, and documentation studies. The results indicate that AI integration, synergized with adequate school infrastructure and an innovative vision, accelerates students' digital citizenship understanding. A unique finding of this study is the successful synchronization of global AI technology with Yogyakarta's local wisdom (the LESUNG philosophy and NGAJENI movement), which serves as an ethical compass for students. Despite challenges related to mental health and cyberbullying, critical AI literacy has proven effective as a risk mitigation instrument. The study concludes that strengthening technology-based critical thinking rooted in local culture is key to forming the Pancasila Student Profile in the digital age.